Impact of night-time symptoms in COPD: a real-world study in five European countries - Price D; Small M; Milligan G; Higgins V; Garcia Gil E; Estruch J (International Journal of COPD, 2013)
David Price,1 Mark Small,2 Gary Milligan,2 Victoria Higgins,2 Esther Garcia Gil,3 Jordi Estruch3 1Centre of Academic Primary Care, University of Aberdeen, Aberdeen, UK; 2Adelphi Real World, Adelphi Mill, Bollington, UK; 3Almirall S.A., Barcelona, Spain Background: Sleep quality is often poor in patients with chronic obstructive pulmonary disease (COPD). A cross-sectional European survey investigated the prevalence of night-time symptoms in COPD to evaluate the level of disconnect between physician and patient perceptions of the presence of night-time symptoms, and to compare the characteristics of patients with and without night-time symptoms. Methods: A total of 251 primary care physicians and 251 respiratory specialists completed record forms on 2,807 patients with COPD. The forms captured information on patient demographics, lung function, COPD severity, and symptoms. Patients completed questionnaires on the time of day when their COPD symptoms bothered them, and the impact of COPD on their ability to get up in the morning and on sleep. Data were compared between groups (those with and without night-time symptoms) using t-tests or Wilcoxon signed rank tests. The kappa statistic was used to assess the level of disconnect between physician and patient perceptions of the impact of night-time symptoms. Results: Most patients (78%) reported night-time disturbance. Patients with night-time symptoms experienced more daytime breathlessness (mean modified Medical Research Council dyspnea scale score 2.4 versus 1.1) and exacerbations in the previous 12 months (mean 1.7 versus 0.4), and received more maintenance therapy (mean of 2.8 versus 2.3 products) than those without. Concordance between the frequency of physician-reported (67.9% of patients) and patient-reported (68.5% of patients) night-time symptoms was good. Physicians significantly underestimated the impact of COPD on the patient's ability to get up in the morning and on sleep (fair–moderate agreement). Physician-reported night-time symptoms were present for 41.2% of patients who could be categorized by Global initiative for chronic Obstructive Lung Disease (GOLD) group (n=937), increasing from 20.9% of those in the low-risk group to 77.4% of those in the high-riskgroup. Conclusion: Patients with COPD experience night-time symptoms regardless of GOLD group, that impact on their ability to get up in the morning and on their sleep quality. Keywords: chronic obstructive pulmonary disease, night-time symptoms, sleep quality, burden